LOKPAL AND JAN LOKPAL IN INDIA AND ITS ROLE IN FIGHT AGAINST CORRUPTION- A STUDY - GM, Jayaramaiah (ShodhKosh: Journal of Visual and Performing Arts, 2024)
There was a time when Gandhiji would say “My religion is based on truth and non-violence. Truth is my God and non-violence is a means of realising him.” Such were the principles of our political leaders at one time. Today what is more astonishing is that India has been ranked 94 on the Corruption Perception Index among 177 countries. While India is at the threshold of becoming superpower, the progress of the country is getting eaten up by the corrupt people of the country. Corruption is closely associated with bribery which means to give or to take profit for some illegal work. Corruption has progressively involved in every sphere of Indian society. Corruption is a cancer that is not restricted to any particular political party. It infects the whole society.